Science or hype? Non-invasive brain stimulation and sport-specific performance: Evidence from a systematic review and three-level meta-analysis - Wang, Q.; Zhong, J.; Bao, H.; Wang, Y. (Journal of Sports Sciences, 2026)
Enhancing athletic performance is a core objective in competitive sports. Non-invasive brain stimulation (NIBS), a set of neuromodulatory techniques, aims to modulate cortical excitability and thereby influence motor and cognitive functions. Despite its commercial appeal and growing application in sports contexts, the empirical evidence supporting its efficacy remains inconclusive. A three-level meta-analysis was conducted to evaluate the effects of NIBS on sport-specific performance and to identify potential moderating factors. The present study included 25 eligible studies and 64 independent effect sizes. Notably, all included studies employed transcranial direct current stimulation (tDCS). The meta-analysis revealed a small but significant overall effect of tDCS on sport-specific performance (Hedges` g = 0.35, p < .01), with considerable heterogeneity across studies (I² = 59.13%). tDCS appeared more effective for open-skill sports (g = 0.63, p < .01) and yielded benefits when targeting motor executive regions (g = 0.56, p < .01). The overall quality of evidence was rated as low. Therefore, while the findings suggest that tDCS may enhance certain aspects of sport-specific performance, the evidence base for NIBS as a whole remains preliminary and methodologically limited. Consequently, the purported performance benefits of NIBS should be interpreted with caution by both researchers and practitioners.